Organic vs. functional neurological disorders: The role of childhood psychological trauma. (January 2017) - Karatzias, Thanos; Howard, Ruth; Power, Kevin; Socherel, Florentina; Heath, Craig; Livingstone, Alison
Abstract: Although the relationship between psychological trauma and medically unexplained symptoms (MUS) is well established, this relationship is less well understood in people with medically unexplained neurological symptoms. In the present study, we set out to compare people with functional neurological disorders, and organic neurological disorders, in terms of childhood and adulthood traumatic events, traumatic stress, emotional dysregulation and symptoms of depression and anxiety. We have hypothesised that those with functional neurological disorders would be more likely to report childhood and adulthood traumatic life events, traumatic symptomatology, emotional dysregulation and symptoms of anxiety and depression, compared to those with organic neurological disorders. Sample consisted of a consecutive series of people with functional neurological disorders and with organic neurological disorders (n = 82) recruited from a hospital in Scotland. Participants completed measures of life events, traumatic stress, emotional regulation, anxiety and depression. The two groups were found to significantly differ in relation to all measures, with the MUS group being more likely to report childhood and adulthood life events, more severe emotional dysregulation, traumatic stress and symptoms of anxiety and stress. Logistic regression analysis revealed that exposure to childhood traumatic life events, specifically childhood sexual abuse, and childhood physical neglect, were the only factors which were significantly associated with membership of the medically unexplained neurological symptoms group. Although further research is required to confirm our findings, our results suggest that identifying and addressing the impact of childhood trauma, may alleviate distress and aid recovery from functional neurological disorders.